Organelle membrane extensions in mammalian cells - Carmichael, Ruth E.; Richards, David; Fahimi, H. Dariush; Schrader, Michael (Biology, 2023)
Organelles within eukaryotic cells are not isolated static compartments, instead being morphologically diverse and highly dynamic in order to respond to cellular needs and carry out their diverse and cooperative functions. One phenomenon exemplifying this plasticity, and increasingly gaining attention, is the extension and retraction of thin tubules from organelle membranes. While these protrusions have been observed in morphological studies for decades, their formation, properties and functions are only beginning to be understood. In this review, we provide an overview of what is known and still to be discovered about organelle membrane protrusions in mammalian cells, focusing on the best-characterised examples of these membrane extensions arising from peroxisomes (ubiquitous organelles involved in lipid metabolism and reactive oxygen species homeostasis) and mitochondria. We summarise the current knowledge on the diversity of peroxisomal/mitochondrial membrane extensions, as well as the molecular mechanisms by which they extend and retract, necessitating dynamic membrane remodelling, pulling forces and lipid flow. We also propose broad cellular functions for these membrane extensions in inter-organelle communication, organelle biogenesis, metabolism and protection, and finally present a mathematical model that suggests that extending protrusions is the most efficient way for an organelle to explore its surroundings.